Educational recommender systems and technologies : practices and challenges - Santos, Olga C., 1978-; Gonzalez Boticario, Jesus (Hershey PA : Information Science Reference, 2012)
'This book aims to provide a comprehensive review of state-of-the-art practices for educational recommender systems, as well as the challenges to achieve their actual deployment'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references and index.
Keywords: Educational technology; Recommender systems (Information filtering).